ANALYSIS OF THE MIDWIFE’S PERFORMANCE AT DR. SAYIDIMAN MAGETAN AFTER AN ACCREDITED HOSPITAL - Srimulti; Sandu Siyoto; Ratna Wardani (Universitas STRADA Indonesia, 2023)
Hospitals that are accredited are a tool to measure the performance of hospitals. The design of this study was qualitative using purposive sampling snowball with the research focus directed at analyzing the performance of midwives at RSUD dr. Sayidiman Magetan after hospital accreditation. With a sample of 7 people and triangulation of 3 people. Based on the results of the study, it can be concluded that in general the performance development of midwives after hospital accreditation has not increased, but the regulations applied at the hospital, for example patient visiting hours have not been fulfilled. The number of midwives is large, but the problem is the use of midwives who are not in accordance with their main duties, for example delivery rooms for supervisors 2, then skilled midwives 4, skilled midwives 16.